Theoretical calculation on a compound formed by methyl alcohol and simmondsin - İzzet KARA; Asli ÖZTÜRK KİRAZ; Halil CETİŞLİ; Ramazan DONAT; Nuri KOLSUZ (International Journal of Secondary Metabolite, 2016)
Etheric oil results from the esterification reactions of oil acids with alcohols. In these reactions, one molecule water (H2O) is composed of H× protons from oil acids and OH- groups which separated from alcohol. Etheric oil is commonly used in food industry, perfume industry and medicine. From this perspective, we need to know physical properties of etheric oil as well as chemical properties. In this study, the highest occupied molecular orbital (HOMO) energies, the lowest unoccupied molecular orbital (LUMO) energies, the electronic properties (total energy, electronegativity, chemical hardness and softness), NBO analysis and thermodynamic parameters of a compound formed by methyl alcohol and simmondsin have been performed by using Gaussian 09W program. The structural and spectroscopic data of the molecule in the ground state have been calculated by using density functional method (DFT/B3LYP) with the 6-31++G(d,p) basis set.